2022
DOI: 10.1021/acs.jcim.2c00092
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based End-to-End Predictions of CO2 Capture in Metal–Organic Frameworks

Abstract: Metal–organic frameworks (MOFs) have become an active topic because of their excellent carbon capture and storage (CCS) properties. However, it is quite challenging to identify MOFs with superior performance within a massive combinatorial search space. To this end, we propose a deep-learning-based end-to-end prediction model to rapidly and accurately predict the CO2 working capacity and CO2/N2 selectivity of a given MOF under low-pressure conditions. Different from previous methods, our prediction model relies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…52 The trend of adsorption isotherms is also essential for screening MOFs. Therefore, we propose an index K (mean trend error) to measure the trend accuracy of adsorption isotherms: GCMC GCMC (9) where n is the number of adsorption points, v prediction is the predicted value of adsorption points, and v GCMC is the simulation value of adsorption points. The smaller the value of k, the more accurate is the prediction of the isotherm trend.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 The trend of adsorption isotherms is also essential for screening MOFs. Therefore, we propose an index K (mean trend error) to measure the trend accuracy of adsorption isotherms: GCMC GCMC (9) where n is the number of adsorption points, v prediction is the predicted value of adsorption points, and v GCMC is the simulation value of adsorption points. The smaller the value of k, the more accurate is the prediction of the isotherm trend.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides, constructing descriptors, also known as feature engineering, is a complex task in machine learning. The relationship between the original data and the adsorption needs to be deeply understood to keep trying to find the best descriptors . The ability to obtain a model with high reliability and validity depends largely on whether the descriptors which reflect the structural properties of the MOFs were chosen adequately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of AI in nanomaterials discovery and design toward developing cleaner energy technologies and achieving a carbon-neutral future has been explored and discussed in some reviews. However, the majority of the previous reviews tend to focus solely on one specific carbon-neutral energy technology (e.g., solar cell , and battery), while others provide inadequate details on the application of AI in nanomaterials discovery and design for these technologies. , Given the extensive use of AI in materials research, a review that summarizes and discusses the application of AI in the design of nanomaterials for various major carbon-neutral energy technologies (e.g., solar cell, hydrogen energy, battery, and CCUS devices) is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) has been very recently used with HTCS to predict the gas adsorption and separation performances of very large numbers of MOFs in a time-efficient manner and to extract the hidden correlations between the structural properties of materials and their gas separation performances . These ML studies focused on CO 2 /CH 4 , CO 2 /N 2 , , CO 2 /H 2 , , O 2 /N 2 , H 2 S/CH 4 , C 3 H 8 /C 3 H 6 , and Xe/Kr separations. For instance, Anderson et al constructed a database of over 400 hypothetical MOFs and showed that ML algorithms can accurately predict the CO 2 /H 2 and CO 2 /N 2 selectivities of these materials using the structural and chemical features of the MOFs as the input.…”
Section: Introductionmentioning
confidence: 99%